2020
DOI: 10.3389/fpsyg.2020.581036
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic, Quarantine, and Psychological Time

Abstract: This article addresses the feeling of strangeness about the perception of time that many people with ordinary lifestyles experienced during the quarantine imposed to fight the presence of COVID-19. It describes different aspects of psychological time affected by the interruption of a normal routine and suggests some cognitive mechanisms, attention, and memory that might have been at play, leading to perceive time as being more or less long. The article also describes the critical role of anxiety and temporal u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 42 publications
1
37
0
4
Order By: Relevance
“…How do restrictions that limit social contact during the Covid-19 pandemic impact our PPT? The Covid-19 pandemic itself and the related social isolation measures present emotionally taxing challenges to many people and might enhance symptoms of depression or negative emotional states 27 . People spend more time at home during a lockdown, leading to repetitive routines lacking diversified events, which, in turn, promotes an unpleasant state of boredom 7 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…How do restrictions that limit social contact during the Covid-19 pandemic impact our PPT? The Covid-19 pandemic itself and the related social isolation measures present emotionally taxing challenges to many people and might enhance symptoms of depression or negative emotional states 27 . People spend more time at home during a lockdown, leading to repetitive routines lacking diversified events, which, in turn, promotes an unpleasant state of boredom 7 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review, Salari and colleagues (2020) analyzed 17 studies from nine countries conducted during the COVID-19 outbreak and showed that the pandemic affected mental health and raised the levels of depression, anxiety, and stress. This increase can be explained by multiple factors: for instance, the World Health Organization (see Grondin et al, 2020) asserted that the more people were exposed to (potentially distressful) news on COVID-19, the higher the reported levels of anxiety and depression were, unless the information were accurate and up-to-date (Wang et al, 2020). Highest levels of anxiety and depression were found in women, young adults, individuals with higher levels of education, and Asians as compared to Europeans (Salari et al, 2020).…”
Section: Psychological Consequences Of the Pandemic Situationmentioning
confidence: 99%
“…The pandemic and the associated routines also affected the perception of time: agendas and routines changed because of the loss of zeitgebers and temporal landmarks, up to a level where the days lost their identity and significance (Grondin et al, 2020). In the UK, Ogden (2020) observed that approximately 40% of the participants indicated that time passed more slowly, and 40% felt it passed more quickly than before the lockdown.…”
Section: Psychological Consequences Of the Pandemic Situationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Covid-19 pandemic is a clear example of a sudden slowdown of our everyday pace, with lockdowns at the societal level impacting the pace of many individual lives, as people navigate new rhythms of living within the confinement of the home. The quarantines, coupled with anxiety and temporal uncertainty, have distorted many people's perception of psychological time (Grondin et al, 2020).…”
Section: Timementioning
confidence: 99%